OTUD5 cooperates with TRIM25 in transcriptional regulation and tumor progression via deubiquitination activity - Fangzhou Li (Nature Portfolio, 2020)
The mechanisms by which deubiquitinases modulate tumour progression are not fully understood. Here, the authors perform an RNAi screen and identify that the deubiquitinase OTUD5 suppresses cancer growth in a TRIM25 dependent manner, which in turn controls the expression of tumour suppressor protein, PML.